PERILAKU DISKRIMINASI MASYARAKAT INDONESIA DI BIDANG HUKUM DALAM NOVEL API TAUHID KARYA HABIBURRAHMAN EL-SHIRAZY (ANALISIS DEKONSTRUKSI) - Abdullah Ali Fauzi (EDU-KATA, 2021)
The aim of study to express discrimination behavioral Indonesian people in law. The research to explain kinds of discrimination behavioral occure in Indonesia. Excerpt in Api Tauhid novel which contain behavioral discrimination is reseach of data. Data is gathered by using dokumentasion, observation, and written method. In the research, the theory is dekonstruksion. The theory of dekonstrustion to use explain kinds of behavioral discrimination in Indonesia with base of excerpt in novel. The result of research in novel is gathered discrimination behavioral to Badiuzzaman Said Nursi character. The kind of discrimination behavioral is authoritative government. Kinds of discrimination behavioral Indonesia people is self law, authoritative government, and bribe to government.